2019
DOI: 10.1590/1982-7849rac2019180221
|View full text |Cite
|
Sign up to set email alerts
|

Keep Innovating: Absorptive Capacity and the Performance of Brazilian Information Technology Companies

Abstract: Continuous innovation is considered a major challenge for companies. By deepening this issue, this article highlights the absorptive capacity, which is the ability to explore external knowledge. This study analyzes the extent to which absorptive capacity affects the organizational performance of Brazilian IT companies. A theoretical model containing three hypotheses related to potential absorptive capacity, realized absorptive capacity, and organizational performance is analyzed by using factor analysis and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
5
0
3
Order By: Relevance
“…Ritala and Hurmelinna-Laukkanen (2013) found that absorptive capacity is responsible for the firm's incremental -more often -and radical innovations. Other authors such as Kostopoulos, Papalexandris, Papachroni and Ioannou (2011), Tavani, Sharifi, and Ismail (2014), Brettel, Greve, and Flatten (2011), and Cardozo, Kronmeyer Filho, and Vaccaro (2019) observed that, in addition to promoting innovation, the absorptive capacity was related to better financial and organizational performance.…”
Section: Exploitationmentioning
confidence: 95%
“…Ritala and Hurmelinna-Laukkanen (2013) found that absorptive capacity is responsible for the firm's incremental -more often -and radical innovations. Other authors such as Kostopoulos, Papalexandris, Papachroni and Ioannou (2011), Tavani, Sharifi, and Ismail (2014), Brettel, Greve, and Flatten (2011), and Cardozo, Kronmeyer Filho, and Vaccaro (2019) observed that, in addition to promoting innovation, the absorptive capacity was related to better financial and organizational performance.…”
Section: Exploitationmentioning
confidence: 95%
“…Devido à relevância do setor para a economia brasileira e as contribuições de Fosfuri & Tribó (2008), Murovec & Prodan (2008), Kostopoulos et al (2011), Thomas & Wood (2014;, Ferreras-Méndez et al (2015), Lau & Lo (2015) e Mitreva et al (2020) sobre a relação entre a capacidade absortiva, a inovação em serviços e o desempenho, esta pesquisa pretende avançar na análise das relações entre estes construtos. Este é um campo de interesse crescente (Cardozo, Kronmeyer Filho, & Vaccaro, 2019;Kale, Aknar, & Başar, 2019) e requer uma maior reflexão por meio de técnicas e de métodos que expandam o conhecimento existente sobre suas relações, bem como em relação a outras variáveis (Bhatti et al, 2021).…”
Section: Introductionunclassified
“…La capacidad de absorción es definida como la habilidad de identificar, asimilar y explotar nuevos conocimientos [14]. Como capacidad dinámica, la capacidad de absorción, es una competencia necesaria para mejorar la innovación mediante la transferencia de conocimiento interno y externo [15].…”
Section: Introductionunclassified